Personal Data Protection Law (comparative \study on Indonesian and Malaysian Law) - Riswandi, Budi Agus; Zulhuda, Sonny; Wibowo, Ari; Hartanto, Ratna; Luthfidyfa, Nabilla Maryam; Erlangga, Vania Lutfi Safira (Universitas Islam Indonesia, 2023)
The book entitled PERSONAL DATA PROTECTION LAW (COMPARATIVE STUDY ON INDONESIAN AND MALAYSIA LAW) is the result of collaborative research between the Faculty of Law of the Islamic University of Indonesia (UII) and Ahmad Ibrahim Kuliyyah of Laws International Islamic University of Malaysia (IIUM). This book consists of three chapters, namely; Chapter 1 Context of Study; Chapter 2. The Concept of Personal Data; Personal Data Protection and Comparison; and Chapter 3 Personal Data Protection Law (Comparative Study on Indonesian and Malaysian Law). Hopefully the publication of this book can add reference and knowledge to the readers. Furthermore, criticism and input for the improvement of this book in the future are highly expected.